IMPLEMENTING EXPERIENTIAL LEARNING IN WRITING CLASS - Ria Yulianti; Achyana Izzatun Nisa (UAD TEFL International Conference)
The objective of this paper is to describe the implementing of experiential leaning in writing class. Writing is the process of expressing ideas into a good writing and composing the ideas into a proper arrangement. Writing is one of language abilities that is taught in the school. The students should be mastered some text types in writing class, such as descriptive text. Descriptive text is a text which says what a particular thing, person or place is like. In the writing process, the students face some problems in writing, such as finding ideas, developing ideas, and arranging ideas into good composition. In this case, the teacher uses a new method to solve that problems. The teachers use experiential learning to enhance the students’ writing. Experiential learning is a learning method where the educators engage the students to learn through experience directly to enhance students’ knowledge and skills. It is also called learning by doing. The steps of implementing experiential learning are doing, reflecting, analyzing, generating and application. In descriptive writing, the students can describe the object easily because they use real experience. The students also feel more enthusiasm in learning process. Therefore, hopefully the students can expand their writing in good construction.